744 Progressively complex neurorehabilitation: from a severe coma to a vegetative state, minimal consciousness ... and the Phoenix bird survives and is reborn from its ashes (Balneo and PRM Research Journal, 2025)
Abstract: Background: Romania has the highest rate of car accidents and deaths per million inhabitants in the European Union, primarily due to poor driving and substandard road conditions. Victims of car accidents often present with complex medical cases involving multiple injuries across various organs, frequently leading to severe complications. Case report. With the approval of the patient's family and the Ethics Committee (no. 19348/25.04.2024) at the Neuromuscular Rehabilitation Clinic, Emergency Hospital "Bagdasar-Arseni," a case study was conducted. A 22-year-old man without a previous medical history suffered severe polytrauma as a result of a road accident. He was transferred to the Neuromuscular Rehabilitation Clinic in a vegetative state (after multiple fractures of the skull base and visceral cranium, with 3 points GCS), atlantoaxial subluxation (requiring cervical collar immobilization), rib fractures, drained hemothorax, near-complete atelectasis of the left lung, status post-pericardial effusion. The medical intervention involved a multifaceted pharmacological approach. Focal intramuscular injections of botulinum toxin targeted specific muscles significantly alleviated spasticity. Special robotic orthoses were used to correct postural abnormalities and maintain the favorable effects of the botulinum toxin. The patient received a personalized and complex nursing rehabilitation program including tracheal stoma management, nutritional support through IV infusions and percutanous gtrostomy (PEG) feeding, re-education of deglutition, intermittent urinary catheterization, and positioning on a special mattress to prevent pressure ulcers. The kinesiotherapy was progressively adapted to the neurologic and general condition. The patient had slight improvements in motor and cognitive abilities, resulting in simple voluntary gestures and affective response schemes. In time, he progressed to a minimally conscious state; he responded to verbal stimuli through blinking and reactive adequate affective mimic in the context of persistent expressive aphasia. He was safely discharged at home. Our main functional objective is the patient’s reinsertion into his family. Ad vitam prognosis and ad functionem outcomes are guarded. Ad laborem prognosis is nil. The patient was periodically reassessed for further rehabilitative care. Conclusions: This case emphasizes the importance of a complex multidisciplinary and patient-centered approach in managing post-traumatic vegetative status following a road traffic accident. The Phoenix symbolically takes steps toward fulfilling its destiny - to survive and gradually rise from its ashesKeywords: vegetative state; spasticity; tetraparesis; traumatic brain injury; botulinum toxin; neurorehabilitation